The indignities of shielding during the COVID-19 pandemic for people with sickle cell disorders: an interpretative phenomenological analysis - Berghs, Maria; Horne, Francesca; Yates, Scott; Kemp, Rachel; Webster, Amy (Frontiers in Sociology, 2024)
This article seeks to understand the first-hand experiences of people with sickle cell, a recessively inherited blood disorder, who were identified as clinically extremely vulnerable during the COVID-19 pandemic. Part of a larger sequential mixed-methods study, this article uses a selective sample of eight qualitative semi-structured interviews, which were analysed using interpretative phenomenological analysis (IPA). The first stage of IPA focused on practical concerns participants had correlated to understanding shielding and their feelings about being identified as clinically extremely vulnerable. In a secondary stage of analysis, we examined the emotions that it brought forth and the foundations of those based on discriminations. This article adds to our theoretical understanding of embodiment and temporality with respect to chronicity and early ageing. It explains how people with sickle cell disorders have an embodied ethics of crisis and expertise. It also elucidates how people’s experiences during the pandemic cannot be seen in void but illustrates ableism, racism, and ageism in society writ large.